Critical Success Barriers (CSB) to Rental Housing Policy Implementation in Urban India - Saha, Debanjali; Banerji, Haimanti; Kumar, Umesh (Alanya Üniversitesi, 2025)
Barriers to rental housing (RH) pose significant challenges to urban development in India. This study examines critical success barriers (CSBs) to implementing RH policies, offering novel insights into this underexplored area. Despite rising demand for RH, significant obstacles hinder effective policy execution. Through expert surveys with 36 respondents and RIDIT analysis, the research identifies and prioritizes 16 CSBs, categorized into Regulatory and Institutional, Economic and Market, and Infrastructure and Development groups. Key findings reveal that the most critical barriers are inflexible rental agreements, negative social attitudes, and the absence of government incentives. These interdependent barriers impact the feasibility, attractiveness, and sustainability of RH projects. Inflexible agreements limit participation, negative social attitudes hinder inclusive development, and lack of incentives reduces private investment. The study recommends revising rental agreements, providing substantial incentives to private investors, and promoting high-density development through modified zoning regulations. Emphasizing multi-level governance, stakeholder engagement, and regular policy evaluations is crucial for effective implementation. Addressing these barriers can enhance the RH sector's sustainability and scalability. This research contributes to the existing literature by providing a quantitative framework for identifying and prioritizing CSBs in the RH, offering valuable insights for policymakers, developers, and stakeholders in urban housing.